Networking with a network: the Liverpool African Committee 1750-1810 - Haggerty, John; Haggerty, Sheryllynne (Cambridge University Press, 2017)
Historians are increasingly using networks as an analytical framework. However, recent research has stressed the inherent problems with networks, including networking institutions. We therefore have to consider why and in what ways actors do, or did, engage with networks. This paper posits a novel interdisciplinary methodology by bringing together regression analysis, visual analytics and history to analyse actors' relationships with an institution, rather than with one another. This methodology, illustrated by the case study of the Liverpool African Committee, 1750-1810, demonstrates that actors' relationships with an institution may be affective or instrumental, reflecting different relationships with, and uses of, the network. Moreover, actors' relationships with an institution are not static and change over time. The methodology and case study presented in this paper suggest a reassesment of our understanding of metropolitan business networking institutions to reflect the complexity of their use.